Perubahan Sosial Masyarakat di Desa Bona, Kecamatan Blahbatuh, Kabupaten Gianyar Pada Masa Pandemi Covid-19 - Ida Bagus Astika Pidada; Anak Agung Inten Mayuni; I Nengah Mileh (Universitas Warmadewa, 2021)
Bona Village is located in Blahbatuh Sub-district, Gianyar Regency. The society of this village lived in agricultural sector that given a lot of benefits and also lontar craft. The kinds of lontar craft are produced, such as: bag, cap, and etc. Lontar craft becomes one of the big opportunities to Bona Village’s society which is interested by foreigners. The result of this craft is marketed in some location, such as: Ubud, Nusa Dua, Kuta, Tabanan, and etc. Since of pandemic covid-19 lontar craft is decreased in sales. Based on the cases, students of KKN Warmadewa University are deemed necessary to do empowerment UMKM in this village. The result of lontar craft is marketed and changed by conventional system to online system by students to aim home industrial product more widely known by society and income increases. Besides that, the implementation of KKN in this village, students participate to prevent the spread of pandemic covid-19 by sharing free mask in crowded places. Then, students do the field activities, such as: cleaning at temple area by giving rubbish bin and dust pan. Students of KKN Warmadewa University do other activities, such as: socialization of marriage early, coloring contest, poster contest, fashion contest and helping students to use zoom application and google classroom. The online activity of KKN-PPM in Bona Village, Blahbatuh Sub-district, Gianyar Regency especially on each program that given by students got a good appreciation by society so it makes this activity is running properly.